Safety, Immunogenicity and Protective Activity of a Modified Trivalent Live Attenuated Influenza Vaccine for Combined Protection Against Seasonal Influenza and COVID-19 in Golden Syrian Hamsters - Ekaterina Stepanova; Victoria Matyushenko; Daria Mezhenskaya; Ekaterina Bazhenova; Tatiana Kotomina; Alexandra Rak; Svetlana Donina; Anna Chistiakova; Arina Kostromitina; Vlada Novitskaya; Polina Prokopenko; Kristina Rodionova; et al. (Vaccines)
Background/Objectives: Influenza viruses and SARS-CoV-2 are currently cocirculating with similar seasonality, and both pathogens are characterized by a high mutational rate which results in reduced vaccine effectiveness and thus requires regular updating of vaccine compositions. Vaccine formulations combining seasonal influenza and SARS-CoV-2 strains can be considered promising and cost-effective tools for protection against both infections. Methods: We used a licensed seasonal trivalent live attenuated influenza vaccine (3×LAIV) as a basis for the development of a modified 3×LAIV/CoV-2 vaccine, where H1N1 and H3N2 LAIV strains encoded an immunogenic cassette enriched with conserved T-cell epitopes of SARS-CoV-2, whereas a B/Victoria lineage LAIV strain was unmodified. The trivalent LAIV/CoV-2 composition was compared to the classical 3×LAIV in the golden Syrian hamster model. Animals were intranasally immunized with the mixtures of the vaccine viruses, twice, with a 3-week interval. Immunogenicity was assessed on day 42 of the study, and the protective effect was established by infecting vaccinated hamsters with either influenza H1N1, H3N2 or B viruses or with SARS-CoV-2 strains of the Wuhan, Delta and Omicron lineages. Results: Both the classical 3×LAIV and 3×LAIV/CoV-2 vaccine compositions induced similar levels of serum antibodies specific to all three influenza strains, which resulted in comparable levels of protection against challenge from either influenza strain. Protection against SARS-CoV-2 challenge was more pronounced in the 3×LAIV/CoV-2-immunized hamsters compared to the classical 3×LAIV group. These data were accompanied by the higher magnitude of virus-specific cellular responses detected by ELISPOT in the modified trivalent LAIV group. Conclusions: The modified trivalent live attenuated influenza vaccine encoding the T-cell epitopes of SARS-CoV-2 can be considered a promising tool for combined protection against seasonal influenza and COVID-19.